Glyphosate does not show higher phytotoxicity than cadmium: Cross talk and metabolic changes in common herb - Kováčik, Jozef; Novotný, Vít; Bujdoš, Marek; Dresler, Sławomir; Hladký, Juraj; Babula, Petr (Journal of hazardous materials, 2020)
Toxicity of glyphosate (G) alone or in combination with cadmium (Cd) was studied in Matricaria chamomilla. Cadmium accumulated in shoots and roots in relation to prolonged exposure while glyphosate and aminomethylphosphonic acid (AMPA) were detected only in roots. After 7 days of exposure, root Cd and G accumulation was similar (56 μg G or 47 μg Cd/g DW in 1 μM treatments and 330 μg G or 321 μg Cd/g DW in 10 μM treatments). Despite this fact, Cd stimulated higher ROS formation and G rather suppressed nitric oxide while H2O2 content was elevated by Cd. Subsequent assay of antioxidative enzymes (SOD, CAT, and APX) showed only the impact of Cd. Non-enzymatic antioxidants revealed more pronounced impact of Cd on ascorbic acid and soluble phenols while non-protein thiols showed synergistic effect of G and Cd in roots. Surprisingly, G alone or in combination with Cd depleted shoot citrate and tartrate accumulation despite no detectable G in shoots. In the roots, Cd evoked expected increase in malate and citrate content while G rather suppressed Cd-induced elevation. These data indicate that glyphosate is less toxic than cadmium but even low G doses are able to induce metabolic changes.
Keywords: Glycine; Antioxidants; Glyphosate; Bioaccumulation; peroxid vodíku; Oxidative Stress; Plant Roots; Environmental risk; Organophosphonates; antioxidancia; kořeny rostlin; Cadmium; kadmium; glyfosát; glycin; Herbicides; oxidační stres; organofosfonáty; Hydrogen Peroxide; Oxidative stress